1993
DOI: 10.1021/ja00072a027
|View full text |Cite
|
Sign up to set email alerts
|

Triplet state and dynamics of photoexcited C70

Abstract: The photoexcited triplet of C70, in toluene, was investigated by time-resolved EPR spectroscopy. Over the entire range of temperatures (8-213 K) the resulting early-time signal is attributed to the polarized EPR triplet spectrum, which evolves in time into a thermalized spectrum. Similar to the case of 3Cío, the narrow liquid-phase spectrum is due to rotational narrowing of the thermal triplet. At both low and high temperatures the results indicate the coexistence of two triplets, differing greatly in their re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
30
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 0 publications
8
30
1
Order By: Relevance
“…(7). This assignment is consistent with values obtained from powder EPR data [5,18,19]. Because the two Gaussians did not reproduce the intensity measured below 70 MHz, a third line centered at 81 (15) MHz and corresponding to the 2E transition, has also been taken into account.…”
Section: Phosphorescence Lifetime Measurementssupporting
confidence: 84%
See 1 more Smart Citation
“…(7). This assignment is consistent with values obtained from powder EPR data [5,18,19]. Because the two Gaussians did not reproduce the intensity measured below 70 MHz, a third line centered at 81 (15) MHz and corresponding to the 2E transition, has also been taken into account.…”
Section: Phosphorescence Lifetime Measurementssupporting
confidence: 84%
“…Surprisingly, the principal value of the ZFS tensor was larger for symbol [60]-fullerene than for [70]-fullerene [18][19][20][21], a result confirmed by many groups irrespective of matrices used. Because of highly polarized EPR spectra, an accurate determination from EPR powder spectra was difficult, leading to quite a large range of reported values.…”
Section: Introductionmentioning
confidence: 68%
“…All TREPR experiments were carried out using a magnetically oriented nematic liquid crystal (LC) as a solvent. Ordering the corroles in LCs allows the deduction of important magnetic, structural and orientational parameters over a wide range of temperatures throughout the nematic fluid phase [29][30][31]. This approach provides a thorough characterization of the corroles photoexcited triplet states, which are involved in oxygen activation [32].…”
Section: Introductionmentioning
confidence: 99%
“…In a series of works, 3 C 70 in glassy matrices had been investigated by electron spin echo (ESE) [18][19][20] and continuous wave (CW) EPR spectroscopy techniques. 16,[21][22][23][24][25][26][27] The temperature change of the 3 C 70 EPR line shape was observed by Closs et al for the first time. 21 Later, Terazima et al and Agostini et al suggested that the temperature change of the EPR line shape occurs due to pseudorotations of 3 C 70 molecules around their larger symmetry axis with correlation times of τ c ∼ 10 −7 -10 −6 s and an activation energy of 250 cm −1 22 and 210 cm −1 .…”
Section: Introductionmentioning
confidence: 74%
“…24 Levanon et al analyzed the time-resolved EPR line shape of 3 C 70 in glassy toluene using the model of the pseudorotations with τ c ∼ 10 −7 s at temperatures 8 K-114 K, and the presence of two types of 3 C 70 triplets with different spin-lattice relaxation (SLR) times T 1 of 0.6 µs and 5 µs was assumed. 23 The model of one triplet was used to simulate the transient EPR line shape at 114 K and below the toluene melting point. 23 Recently, the CW EPR line shape of 3 C 70 at 70 K was simulated using a distribution of zero-field splitting (ZFS) parameters D and E within an ensemble of frozen 3 C 70 .…”
Section: Introductionmentioning
confidence: 99%